Assessing the genetic diversity of rice originating from Bangladesh, Assam and West Bengal - Travis, Anthony J.; Norton, Gareth J.; Datta, Sutapa; Sarma, Ramendra; Dasgupta, Tapash; Savio, Filipe L.; Macaulay, Malcolm; Hedley, Peter E.; McNally, Kenneth L.; Sumon, Mahmud H.; Islam, M. Rafiqul; Price, Adam H. (Springer, 2015)
Genetic diversity among rice cultivars from Bangladesh and North East India was assessed using a custom 384-SNP microarray assay. A total of 511 cultivars were obtained from several sources, choosing landraces likely to be from the aus subpopulation and modern improved cultivars from Bangladesh. Cultivars from the OryzaSNP set and Rice Diversity Panel 1 (RDP1) were also included for reference.